Triple-GEM detectors gas mixture studies. (26th October 2021) - Corbetta, M.; Guida, R.; Mandelli, B.
Abstract: Good and safe long-term operation of gaseous detectors are mainly guaranteed by the quality and stability of their gas mixture. Among Micro Pattern Gaseous Detectors (MPGD), Triple Gas Electron Multipliers (Triple-GEMs) have lately been more and more considered as tracking devices for LHC Experiments Muon Systems, as well as for others physics applications. Triple-GEM detectors are commonly operated with Ar/CO2 or Ar/CO2 /CF4 gas mixtures, and the correct proportion between the different gas mixture components is fundamental for stable detector operation. Moreover, common impurities such as N2, O2 and H2 O can affect their performance, mining their response reliability. This study presents a characterization of Triple-GEM detectors performance in relation to their gas mixture composition. Results are reported in terms of experimental measurements as well as computer simulations of the Triple-GEM electron amplification process.